(untitled) (Shikshya Sandesh, 2023)
The aim of this study is to investigate the khambus of Nepal with the focus on the ancestral rites clan and culture. The Khambu Rais or Rais are one of the most ancient indigenous ethnolinguistic groups of Nepal. who used to live in wallo kirant and majh kirant for particular reason. khambus are nature worshippers. Culture is something that people actively create, and it soon helps to shape a population’s sense of self. The myths, tales, shared origin, and cultural history helped to validate and solidify the group’s identity. In this article, stated about khambus and their traditional culture and rituals, despite the fact that they currently incorporate various mainstream religions and rituals. Khambuwan is called majh Kiratand wallo Kirat. khambus called Kirat Rai. Kirata is a generic term for Mongoloids and thus was used in numerous Sanskrit and classical texts as well as some Indian epigraphs. ‘Rai’ is a derivative of Raja. This title is said to have been conferred on the Khambu chiefs by Prithivinarayan shah after the Gorkha conquest of Khambuwan, Although the Khambu are typically thought of as a single organization, a look at their background would show that they actually consist of countless smaller groupings known as thars. Based on their social structure. The Khambu are examined for their differences and similarities in this essay. The Khambu society’s cultural facets can be revealed by an effort to comprehend the intricate nature and operation of the thars and rituals. This study, Philosophy. Uses interpritivism because it retains the purpose of understanding and interpret a research perspective on the sources and factor about khambu society and it’s culture and clan. Nature of Sources of data will be qualitative. Fact will be analysis by primary and secondary sources. Finding of this essay is khambu are still existence with unity in diversity clan by culture.